2019
DOI: 10.32553/ijmbs.v3i11.714
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Excessive Postnatal Weight Loss in Healthy New-Borns. Will Continuous Temperature Monitoring Help?

Abstract: Objective: To study if continuous temperature monitoring helps to prevent excessive postnatal weight loss in healthy newborns during hospital stay. Design: Prospective randomised controlled trial Setting: Postnatal ward of a tertiary level hospital in south-west India, between July 2018 and October 2018. Participants: 515 healthy newborns born in the hospital during the study. Intervention: Mothers were given the BEMPU device within 24 hours of delivery and  taught to recognize alarms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Using the TempWatch for 4 weeks has been shown to promote parental compliance to skin-to-skin contact and neonatal weight gain during the first and fourth weeks of use (85). Across hospital and community settings, the device has also been shown to be accepted well by doctors and families (86), and has not been reported to cause any adverse effects to the neonate (85,87). Since the TempWatch is a relatively new device, further research is needed to validate these early findings.…”
Section: Bempu Tempwatchmentioning
confidence: 99%
“…Using the TempWatch for 4 weeks has been shown to promote parental compliance to skin-to-skin contact and neonatal weight gain during the first and fourth weeks of use (85). Across hospital and community settings, the device has also been shown to be accepted well by doctors and families (86), and has not been reported to cause any adverse effects to the neonate (85,87). Since the TempWatch is a relatively new device, further research is needed to validate these early findings.…”
Section: Bempu Tempwatchmentioning
confidence: 99%
“…Neonates who were admitted to cial care nursery (SCN) or neonatal intensive care unit (NICU) soon after birth cluded, unless they were returned to the postnatal wards within 48 h of life. Rea neonates requiring SCN admission soon after birth included prematurity of less Studies evaluating the BEMPU TempWatch in LMICs have shown that it is highly accurate at detecting hypothermia [10], promotes neonatal weight gain and SSC, and causes no adverse effects in the neonate [11,12]. However, its usefulness in a high-income country setting has not been evaluated.…”
Section: Patientsmentioning
confidence: 99%
“…It is targeted for use in low-and income countries (LMICs), with its simple-to-use design intended to be understo by parents with low education levels who may be unaware of their baby's risk thermia [9]. Studies evaluating the BEMPU TempWatch in LMICs have shown that it accurate at detecting hypothermia [10], promotes neonatal weight gain and S causes no adverse effects in the neonate [11,12]. However, its usefulness in a high country setting has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%